Settlement of Disputes Due to Default on the Ground of Force Majeure: A Review Based on Articles 1244 and 1245 of the Civil Code - Hanim, Lathifah; Prasetia Wiranto, Agus (Jurnal Hukum Khaira Ummah, 2026)
Force majeure is often used as a reason for debtors to escape responsibility for failure to fulfill their obligations (default). This study aims to analyze the criteria for circumstances that can be categorized as force majeure and how the dispute resolution mechanism for default arising from it is based on the perspective of Article 1244 and Article 1245 of the Civil Code (BW). The research method used is normative juridical with a statutory approach and a conceptual approach. The results show that Articles 1244 and 1245 of the BW provide legal protection for debtors to avoid paying costs, damages, and interest, provided that the debtor can prove the existence of an event beyond their control that could not have been predicted beforehand. However, the application of these articles in disputes often creates ambiguity regarding the boundaries between the difficulty of contract implementation (hardship) and the impossibility of contract implementation (impossibility). Dispute resolution in this area ideally prioritizes the principle of good faith through contract renegotiation to achieve a win-win solution before resorting to litigation.